Pengaruh Fleksibilitas Kerja dan Spesialisasi Pekerjaan Terhadap Kinerja Karyawan pada PT. Pertamina Patra Niaga-Regional Kalimantan - Nurhayati, Fitri; Lestari, Dirga (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effect of work flexibility and job specialization on employee performance at PT. Pertamina Patra Niaga Regional Kalimantan. This research used a quantitative method with data collection techniques through questionnaires distributed to employees in the marketing division. The population in this study consisted of 40 employees, and all members of the population were used as samples through saturated sampling techniques. The data analysis techniques used were validity test, reliability test, multiple linear regression analysis, t-test, F-test, and coefficient of determination using SPSS version 21. The results showed that work flexibility had a positive but insignificant effect on employee performance with a significance value of 0.813 > 0.05. Meanwhile, job specialization had a positive and significant effect on employee performance with a significance value of 0.002 < 0.05. Simultaneously, work flexibility and job specialization significantly affected employee performance with an F-count value of 7.567 and a coefficient of determination value of 29.0%. Based on these results, it can be concluded that job specialization has a more dominant influence on improving employee performance at PT. Pertamina Patra Niaga Regional Kalimantan.